1991
DOI: 10.1093/bja/67.4.464
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Preoxygenation in Morbidly Obese Patients

Abstract: The time taken for the oxygen saturation (SpO2) to decrease to 90% after preoxygenation was studied in six morbidly obese patients and six matched controls of normal weight. During apnoea the obese patients maintained Spo2 greater than 90% for 196 (SD 80) s (range 55-208 s), compared with 595 (SD 142) s (range 430-825 s) in the control group (P less than 0.001). One patient in the obese group had desaturation before the onset of complete relaxation and tracheal intubation, without complications. Bedside lung f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(34 citation statements)
references
References 0 publications
1
31
0
2
Order By: Relevance
“…Comparing the values obtained in our unit when identical blood samples were analysed using the laboratory analyser, an arterial blood gas machine, and a handheld blood glucose meter, we found up to a 4 mmol.l )1 difference, with the handheld meter performing least accurately, especially at lower blood glucose concentrations. Similar discrepancies have been reported by others [2][3][4].…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Comparing the values obtained in our unit when identical blood samples were analysed using the laboratory analyser, an arterial blood gas machine, and a handheld blood glucose meter, we found up to a 4 mmol.l )1 difference, with the handheld meter performing least accurately, especially at lower blood glucose concentrations. Similar discrepancies have been reported by others [2][3][4].…”
supporting
confidence: 91%
“…Several recent papers have investigated desaturation (S a O 2 < 90%) in morbidly obese patients. Berthoud et al [2] found that after 3 min pre-oxygenation, morbidly obese (BMI > 35 kg.m )2 ) patients desaturated within 196 s, significantly faster than their control group of normal sized patients (595 s). One patient with a BMI of 58.4 kg.m )2 desaturated to 90% after only 55 s, and to 82% in 65 s. These findings are broadly in agreement with Jense et al [3] who studied time to desaturation after 5 min of pre-oxygenation.…”
Section: A Replymentioning
confidence: 99%
See 1 more Smart Citation
“…Even with preoxygenation, the duration of apnea prior to desaturation can be anticipated to be significantly shorter in the morbidly obese than in patients of normal weight. 32 Preoxygenation is considered to be sufficient when the end-tidal oxygen fraction is [ 90%. 33 Tidal volume breathing through a well-sealed face mask for three minutes or four vital capacity breaths are common techniques of preoxygenation.…”
Section: Positioning and Preoxygenationmentioning
confidence: 99%
“…Même avec une préoxygénation, on peut prévoir que la durée de l'apnée avant désaturation sera significativement plus courte chez le patient obèse morbide que chez un patient de poids normal. 32 La préoxygénation est considérée comme suffisante lorsque la fraction d'oxygène télé-expiratoire est [ 90 %. 33 La respiration en volume courant via un masque facial bien scellé pendant trois minutes ou quatre respirations en capacité vitale sont deux techniques de préoxygénation courantes.…”
Section: Positionnement Et Préoxygénationunclassified